Inclusive Workplace Culture of a Government Office in the Philippines Through Intercultural Communication - Jherico R. Gamboa; John Feree C. Arriola; Jade Chrisel L. Baquiran; Jesus P. Briones; Marmelo V. Abante (Humanities, Society, and Community, 2024)
Effective intercultural communication is essential in the workplace to address cultural barriers, improve inclusivity and promote employee engagement. In this respect, the study aimed to enhance cultural competence by observing emotions, developing cultural sensitivity, and identifying barriers to intercultural communication within a government office in the Philippines. This study examined the cognitive aspects of intercultural communication and barriers to effective interaction among employees. A comprehensive quantitative-descriptive study was conducted with a census of fifty (50) employees from the subject government office, including permanent staff and outsourced personnel. The data-gathering tool was a validated questionnaire distributed via an in-person survey. The data were analyzed using frequency, percentage, weighted mean, and Spearman’s rank correlation coefficient. The findings indicate that respect for cultural differences is highly practiced in the office, with the cognitive interaction aspects of intercultural communication to be further improved for a more efficient inclusive environment. Although barriers to intercultural communication exist, they can be minimized by fostering respectful and inclusive interactions among employees. Based on the findings of the study, a strategy roadmap for improving intercultural communication is proposed. This study is essential for an organization seeking to improve workplace dynamics and the long-term success created through diversity and inclusion initiatives.